Thalidomide maintenance therapy maturates the T cell compartment and compromises antigen-specific antitumor immunity in patients with multiple myeloma - Krämer, Isabelle; Witzens-Harig, Mathias; Hose, Dirk; Meißner, Tobias; Neuber, Brigitte; Engelhardt, Melanie; Haas, Jürgen; Neben, Kai; Ho, Anthony Dick; Goldschmidt, Hartmut; Hundemer, Michael (Experimental hematology, 2013)
Interferon (INF)-α was the maintenance treatment of choice after autologous stem cell transplantation in multiple myeloma in the past, but currently Thalidomide is commonly used. In this prospective study, the implications of the various types of maintenance therapy on the patients T cell pattern and activation status were assessed. T cells were analyzed for expression of surface molecules, cytokine secretion, the presence of regulatory T cells, and the specific activation against the multiple myeloma antigen HM1.24. T cells from 69 multiple myeloma patients were analyzed: 19 patients were treated with IFN-α; 26 were treated with Thalidomide; and 24 patients received no maintenance therapy. Specific T cell activation with an immunogenic HLA-A2+-restricted peptide from the myeloma-associated antigen HM1.24 was impaired in the Thalidomide group. In accordance with this observation, there was a trend toward a higher amount of regulatory T cells in the Thalidomide group. Furthermore, patients treated with IFN-α showed high rates of naive T cells, whereas a high rate of effector memory T cells was observed in the Thalidomide group. Importantly, after cessation of Thalidomide therapy, this effect was reversible in the CD8 compartment. In conclusion, Thalidomide maintenance therapy has profound implications on T cell pattern and activation status, which compromise antigen specific antitumor immunity.